Inulin-producing Genes in Gembili (Dioscorea esculenta) and Future Applications for Food Industries in Indonesia - Pramanda, Ihsan Tria; Anjani, Dellamartha; Heriawan, Gili (Indonesian Journal of Life Sciences, 2022)
Inulin can be found in abundance in nature, this form of carbohydrate (fructans) is utilized by plants as an energy storage and possibly for other uses. Human use inulin as a dietary fiber and prebiotics to improve the health of their digestive system or to improve the physicochemical and sensory properties of foods. Gembili (Dioscorea esculenta) is a type of yam that grows well in Indonesia and contains inulin up to 14.77% of its dry weight. The current state of inulin production utilizes conventional extraction from tubers; thus, the demands of the market cannot be satisfied, and the price skyrocketed. Biotechnological approaches such as incorporating genes that encodes the enzymes involved in inulin biosynthesis into bacteria or yeasts can be exploited to improve the yield and sustainability. The biosynthesis of inulin involves three main genes 1-SST, 6-SFT and 1-FFT. Genetic information of the gene responsible for the biosynthesis of inulin in Gembili needs to be elucidated.